Diagnosis of a Rare Rickettsia felis Infection Complicated with Unusual Pericardial Effusion and Cardiac Tamponade Using an mNGS Test - Tien-Lung Po; Chien-Hsien Huang; Chia-Hsun Lin; Huei-Fong Hung (Case Reports in Infectious Diseases)
The occurrence of sporadic rickettsial infections has been consistently undervalued and overlooked, primarily owing to a limited emphasis on routine examinations for rickettsioses in clinical practice. At present, the immunofluorescence assay is the prevailing diagnostic method for suspected rickettsioses that enables the detection of specific antibodies against rickettsia in human serum. Herein, we present an exceptional instance of rickettsial infection that was characterized by a rare manifestation of extensive pericardial effusion leading to dyspnea and cardiac tamponade. A diagnosis of chronic fibrosing pericarditis was established based on pericardium tissue obtained through pericardiotomy, and a conclusive metagenomic next-generation sequencing test confirmed the presence of Rickettsia felis infection. The cat flea, scientifically known as Ctenocephalides felis, is the predominant carrier of R. felis. An escalating incidence of human R. felis infections has raised concerns, particularly in light of the burgeoning population of domesticated animals in many contemporary societies.